Parenting the strong-willed child : the clinically proven five-week program for parents of two- to six-year-olds - Forehand, Rex L. (Rex Lloyd), 1945- (McGraw-Hill, 2010)
Rex Forehand, Ph. D. and Nicholas Long Ph. D. have helped thousands of parents achieve discipline using positive reinforcement, without yelling or harming the child's self-esteem. Their clinically proven, five-week program gives you the tools you need to successfully manage your child's behavior, giving specific factors that cause or contribute to disruptive behavior; ways to develop a more positive atmosphere in your family and home; and strategies for managing specific behavior problems. The completely revised and updated edition includes: new information, based on research, about child temperament; new chapter on the hot topic of play as a means of strengthening parent-child relationship; new section on collaborative disciplining with preschool teachers; expanded section about depression and stress linked to parenting; new research findings about ADHD and its treatment.